ANALISA PENGARUH FILTER WARNA DAN DAYA LAMPU FLUORESCENT TERHADAP KELAJUAN NYAMUK - Gita Rahayu; Saktioto Saktioto (Komunikasi Fisika Indonesia, 2018)
Mosquitoes are insects that can cause dangerous problems to human health. Therefore, mosquitoes need to be identified based on its motion so it can stay away from human. The purpose of this research is to investigate the effect of power and color spectrum of lamp toward mosquito speed. This research used optical method based on light beam that affected mosquitobody. This research designed a radiation system inside a glass box with thickness of 0,5 cm size (30x7x20) cm. Five mosquitoes were irradiated by light from fluorescent lamp with power 11 Watt and 26 Watt that have been filtered using red, orange, yellow, green, blue and purple color plastics. The radiation process was recorded using a digital camera about 26 minutes. The recorded video was processed using Tracker program. The Tracker program analyzedthe mosquito speed based on its displacement from one to another position. The results showed that mosquito highest speed at unfiltered light, red, blue and purple colors occurred when irradiated with 26 Watt lamp while at color of orange, yellow and green occured when irradiated with 11 Watt lamp. Mosquitoes highest speed value when irradiated by orange, yellow and green are 0,632 m/s, 0,693 m/s and 0,645 m/s. Mosquitoes lowest speed value when irradiated by blue and purple light are 0,308 m/s and 0,285 m/s. The speed of the mosquitoes when irradiated by red and unfiltered lights are 0,517 m/s and 0,541 m/s respectively. The data showed that mosquitoes moved away from light source when irradiated by unfiltered lights, red, blue and purple while mosquitoes approached the light source when irradiated by orange, yellow and green light.